International Trade in Latin America: The Logistics Performance Index and the Transport of Maritime Containers (2010-2018) - Gutiérrez Ortiz, Ariel; López Alvarado, Noé; Silva Aguilar, Germán Israel (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To determine the relationship between the logistics performance index with respect to the movement of maritime containers in Latin American countries.MATERIAL AND METHOD: This is a quantitative, research with a correlational and explanatory scope. Two variables are used, one from the World Bank and the other from the Economic Commission for Latin America and the Caribbean [ECLAC], considering the ten most relevant countries in the movement of containerized cargo, according to ECLAC (2021). Pearson's correlation coefficient is used to know the relationship of the variables and their possible explanation.RESULTS: Chile, Ecuador, Mexico, and Panama show a considerable positive relationship between the two variables. The logistics performance index between 2010 and 2018 is a slightly explanatory variable of the behavior of the transport of containers.CONCLUSIONS: In general terms, it is imperative that Latin American countries develop strategies and actions that allow them to optimally improve and increase customs and port infrastructure, logistics competence, merchandise monitoring, time management for the distribution of goods in an agile manner and the attraction of containerized merchandise.
Keywords: Containerized cargo; Merchandise trade; Maritime sector.